Expression of auxin transporter genes in flax (Linum usitatissimum) fibers during gravity response - N. N. Ibragimova; N. E. Mokshina (Вавиловский журнал генетики и селекции, 2024)
Gravitropism is an adaptive reaction of plants associated with the ability of various plant organs to be located and to grow in a certain direction relative to the gravity vector, while usually the asymmetric distribution of the phytohormone auxin is a necessary condition for the gravitropical bending of plant organs. Earlier, we described significant morphological changes in phloem fibers with a thickened cell wall located on different sides of the stem in the area of the gravitropic curvature. The present study is the first work devoted to the identification of genes encoding auxin transporters in cells at different stages of development and during gravity response. In this study, the flax genes encoding the AUX1/LAX, PIN-FORMED, PIN-LIKES, and ABCB auxin transporters were identified. A comparative analysis of the expression of these genes in flax phloem fibers at different stages of development revealed increased expression of some of these genes at the stage of intrusive growth (LusLAX2 (A, B), LuxPIN1-D, LusPILS7 (C, D)), at the early stage of tertiary cell wall formation (LusAUX1 (A, D), LusABCB1 (A, B), LusABCB15-A, LusPIN1 (A, B), LusPIN4-A, and LusPIN5-A), and at the late stage of tertiary cell wall development (LusLAX3 (A, B)). It was shown that in the course of gravitropism, the expression of many genes, including those responsible for the influx of auxin in cells (LusAUX1-D), in the studied families increased. Differential expression of auxin transporter genes was revealed during gravity response in fibers located on different sides of the stem (upper (PUL) and lower (OPP)). The difference was observed due to the expression of genes, the products of which are responsible for auxin intracellular transport (LusPILS3, LusPILS7-A) and its efflux (LusABCB15-B, LusABCB19-B). It was noted that the increased expression of PIN genes and ABCB genes was more typical of fibers on the opposite side. The results obtained allow us to make an assumption about the presence of differential auxin content in the fibers of different sides of gravistimulated flax plants, which may be determined by an uneven outflow of auxin. This study gives an idea of auxin carriers in flax and lays the foundation for further studies of their functions in the development of phloem fiber and in gravity response.